2019
DOI: 10.1128/aac.02356-18
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of pSK1 Family Plasmids and Enhanced Chlorhexidine Tolerance in a Dominant Hospital Lineage of Methicillin-Resistant Staphylococcus aureus

Abstract: Staphylococcus aureus is a significant human pathogen whose evolution and adaptation have been shaped in part by mobile genetic elements (MGEs), facilitating the global spread of extensive antimicrobial resistance. However, our understanding of the evolutionary dynamics surrounding MGEs, in particular, how changes in the structure of multidrug resistance (MDR) plasmids may influence important staphylococcal phenotypes, is incomplete.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 63 publications
4
18
0
Order By: Relevance
“…pGO1evol 2 and pGO1evol 3 also exhibited reduction via recombination between these sites. These data are consistent with others’ observations that IS elements facilitate distinct remodelling strategies for the evolution of medium-to-large composite plasmids 27 .…”
Section: Resultssupporting
confidence: 93%
“…pGO1evol 2 and pGO1evol 3 also exhibited reduction via recombination between these sites. These data are consistent with others’ observations that IS elements facilitate distinct remodelling strategies for the evolution of medium-to-large composite plasmids 27 .…”
Section: Resultssupporting
confidence: 93%
“…Conversely, a strain with a lower plasmid copy number would produce less QacR, and thus qacA expression could be higher due to a decrease in the amount of the repressor. Intriguingly, this regulatory model also explains the increased resistance seen upon qacA and qacR integration into the chromosome (48); in a single copy, smaller amounts of functional QacR dimers would lead to increased expression of qacA and thus increased CHX resistance. Future targeted mechanistic studies will seek to investigate the proposed regulatory model.…”
Section: Discussionmentioning
confidence: 90%
“…For example, CHX is a well-tolerated antiseptic that has been shown to be effective as a presurgical skin preparation. Though prior thought suggested that antiseptic resistance was unlikely (7), the ubiquitous use of CHX in hospitals and the community has led to the appearance of strains of bacteria, including S. aureus, that are more resistant to CHX (9,48). Furthermore, the increasing presence of QACs such as BKC in everyday personalcare products appears to have provided an additional selection for efflux-mediated antiseptic resistance in bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acquisition of these different genetic elements in a single large plasmid can enhance adaptation and dissemination of S. aureus in different environments due to co-selective advantage (Wall et al, 2016). A recent study investigating ST239 MRSA strains evolution over the last 32 years revealed that plasmids coevolved with strains and enhanced resistance to multiple antibiotics (Baines et al, 2019).…”
Section: Introductionmentioning
confidence: 99%